Does Quality Adjustment Matter for Technologically Stable Products? An Application to the CPI for Food - Greenlees, John S; McClelland, Robert (American Economic Review, 2011)
Most indexes in the Consumer Price Index (CPI) use a form of the “matched-model” approach. It is frequently assumed that this approach accurately reflects inflation for items that have no major trend in quality. In this paper we investigate that hypothesis using CPI data for retail food items. We find that CPI analysts may be correct on average when they decide that new and replacement items are similar in quality. We also find, however, that when sample items are replaced by items of significantly different quality the CPI imputation procedures may underestimate price change and overstate quality change.